2,2-Dichloro-N-(2,5-dichlorophenyl)acetamide - B. Thimme Gowda; Sabine Foro; Hartmut Fuess (Acta Crystallographica Section E, 2008)
The conformation of the N—H bond in the title compound, C8H5Cl4NO, is syn to the 2-chloro substituent and anti to the 5-chloro substituent in the aromatic ring. The bond parameters are similar to those in 2,2-dichloro-N-phenylacetamide and other acetanilides. In the crystal structure, the molecules are linked into chains through N—H...O hydrogen bonding.